Clinical Assessments as Predictors of Primary On-Road Outcomes in Parkinson's Disease. (October 2015) - Classen, Sherrilene; Holmes, Jeffrey D.; Alvarez, Liliana; Loew, Katherine; Mulvagh, Ashley; Rienas, Kayla; Walton, Victoria; He, Wenqing
Parkinson's disease (PD) is a neurodegenerative disorder that affects fitness to drive. Research that has examined clinical predictors of fitness to drive in PD, using the on-road assessment as the gold standard, has generally used a dichotomous pass/fail decision. However, on-road assessments may also result in one of two additional outcomes (pass with recommendations, or fail-remediable). Individuals within these subgroups may benefit from interventions to improve their fitness to drive abilities. This study investigated clinical predictors that could be indicative of the pass, pass with recommendations, or fail-remediable categories for drivers with PD ( N = 99). Trails B, Left Finger to Nose Test, and contrast sensitivity measures were identified as significant predictors for the pass, and pass with recommendations subgroups. No significant predictors were identified for the fail-remediable subgroup. Results from this study provide a foundation for clinicians to identify drivers who can benefit from recommendations to preserve their driving abilities.